2020
DOI: 10.1016/j.mehy.2020.109934
|View full text |Cite
|
Sign up to set email alerts
|

The effects of allium sativum on immunity within the scope of COVID-19 infection

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website. Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre-including this research content-immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 30 publications
1
75
0
3
Order By: Relevance
“…The trial showed that garlic can upregulate immune response genes and activate apoptosis and the xenobiotic metabolism in people who regularly consume garlic containing meals ( Charron et al, 2015 ). The anti-inflammatory and immunomodulatory potential of garlic was also subject to a most recent publication indicating that garlic may be beneficial as a preventive measure in the current COVID-19 pandemic ( Donma & Donma, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The trial showed that garlic can upregulate immune response genes and activate apoptosis and the xenobiotic metabolism in people who regularly consume garlic containing meals ( Charron et al, 2015 ). The anti-inflammatory and immunomodulatory potential of garlic was also subject to a most recent publication indicating that garlic may be beneficial as a preventive measure in the current COVID-19 pandemic ( Donma & Donma, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…4,[127][128][129][130][131][132][133][134][135] These include Withania somnifera (Indian ginseng, Ashwagandha), [136][137][138] Curcuma longa (curcuma/turmeric), 130,138 Allium sativum (garlic), 132 Camellia sinensis (green tea), 139 Glycyrrhiza glabra (licorice), 130,133,140 Tinospora cordifolia (guduchi), 141 and others. 4,131,135 Some of the active constituents include phenolics, 139 flavonoids, 142 alkaloids, 143 saponins and steroids 144 and many more. 135 Glycyrrhizin, 145 glycyrrhizic acid, 130 catechin and curcumin 146 are some of the important active principles in few medicinal plants (Licorice, turmeric) believed to be effective against SARS-CoV-2.…”
Section: Immune Modulatorsmentioning
confidence: 99%
“…In einer neueren Studie aus 2016 mit einem "Aged Garlic"-Extrakt konnte an 120 Teilnehmern (ebenfalls über 3 Monate) keine Reduzierung der Inzidenz von Infekten beobachtet werden, allerdings wurden in der Interventionsgruppe deutlich weniger Symptome berichtet und auch hier war die Dauer der Erkrankung im Schnitt geringer [21]. Vorgeschlagen werden hinsichtlich Covid-19 günstige Wirkungen auf das Immunsystem [6]. Die Große Kapuzinerkresse (T. majus L.) ist erst in den 1680er-Jahren in Europa greifbar, erstmals 1687 beschrieben von Paul Hermann, Professor für Botanik in Leiden.…”
Section: Knoblauch Und Zwiebelnunclassified